A Study of Idioms Containing Terms for Plants in English and Vietnamese - Hoàng Thị Nhung (2011)
Idioms in general and idioms containing TsFPs in particular are of culture-specific nature and vary from culture to culture. On this basis, the thesis investigates the similarities ….